Ecological Apocalypse in The Three Poems: We Think We Are Less Foolish, Crossing A City Highway, and Epithalamia - Eko Wijaya; Delvi Wahyuni (English Language and Literature, 2020)
AbstractWijaya, Eko. 2020. Ecological Apocalypse in the Three Poems: We Think We Are Less Foolish, Crossing A City Highway, and Epithalamia. Thesis. English Department. Faculty of Languages and Arts. Universitas Negeri Padang.            This thesis is the analysis of the three poems: We Think We Are Less Foolish, Crossing A City Highway, and Epithalamia. It explores the issue of ecological apocalypse which is done by people toward the nature. It is also intended to know the contribution of poetic elements: imagery, irony, and speaker in revealing the issue of ecological apocalypse. This analysis is related to the concept of eco-criticism by Garrard, McKusic, Barry, and Buell that is supported by the text-based and context-based interpretation. The result of this analysis shows about ecological apocalypse is a result of human intervention. They exploit and pollute the nature continuously just for their own advantages without concern about the sustainability of nature.Key words: apocalypse, human, nature, anthropocentrism, exploitation, pollution.